Effect of Ni/Malaysian dolomite catalyst synthesis technique on deoxygenation reaction activity of waste cooking oil - Hafriz R.S.R.M.; Shafizah I.N.; Arifin N.A.; Salmiaton A.; Yunus R.; Yap Y.H.T.; Shamsuddin A.H. (Elsevier Ltd, 2023)
Carbon dioxide; Catalyst activity; Fourier transform infrared spectroscopy; Fuels; Gas chromatography; High resolution transmission electron microscopy; Liquid chromatography; Magnesia; Mass spectrometry; Oils and fats; Physicochemical properties; Precipitation (chemical); Scanning electron microscopy; Temperature programmed desorption; Catalyst synthesis; Deoxygenation reactions; Deoxygenations; Dolomite; Malaysians; Reaction activity; Renewable fuels; Synthesis techniques; Waste cooking oil; ]+ catalyst; Pyrolysis; catalysis; catalyst; chemical reaction; desorption; detection method; dolomite; nickel; pyrolysis